Potential Attractiveness of Coffee Agro-Tourism in Jarai Sub-District, Lahat Regency - Anggraini, Meisya; Karo Karo, Pelliyezer; Lesmana, Andhika Chandra; Wibowo, Budi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
Nowadays, to preserve coffee, many coffee plantations are developed into agritourism so that tourists are interested in visiting coffee plantations. The purpose of agritourism is not only for recreation, but also to gain new experiences, knowledge, and business relationships in agriculture. The purpose of this study was to determine the Potential Attractiveness of Coffee Agro-tourism in Jarai District, Lahat Regency. The research method used in this research is Qualitative research method. The results obtained show that Jarai District has great potential in the coffee agritourism sector. Despite having significant potential, the development of agritourism in Jarai District faces several challenges, such as limited accessibility to the plantation area, lack of supporting tourism facilities such as lodging and dining, and lack of promotion. The people of Jarai Sub-district, especially the coffee farmers, show great interest in participating in the development of coffee agritourism. Based on the SWOT analysis, optimal development strategies include improving facilities and accessibility, diversifying tourism products and experiences, and strengthening digital promotion.